A critical assessment of design tools for stress analysis of adhesively bonded double lap joints. Issue 8 (18th April 2021) - Stapleton, Scott E.; Stier, Bertram; Jones, Stephen; Bergan, Andrew; Kaleel, Ibrahim; Petrolo, Marco; Carrera, Erasmo; Bednarcyk, Brett A.
Abstract: Despite the proliferation of high fidelity finite-element (FE) models, lower fidelity models remain commonly used in adhesively bonded joint design. These design models can save both computational and user time due to their simplicity and ease of use. This study presents a detailed assessment of local stress fields predicted by five design models: A4EI, HyperSizer, Joint Element Designer, Carrera Unified Formulation, and a Continuum Solid Shell FE model. All models were compared with a high fidelity, dense mesh FE model. Six double lap joint cases with different combinations of features like different adhereds, a core, and tapers were compared.